Mapping military roles in COVID-19 responses in Latin America: contours, causes and consequences - Macias-Weller, Ariam; Croissant, Aurel (HCIAS working papers on Ibero-America, 2022)
This is an explorative analysis of military roles in COVID-19 government responses in Latin America. We conceptualize the military’s involvement along fifteen categories of COVID-19 related roles and missions. Based on this conceptualization we assess the extent of military engagement in containing the disease in 17 countries. Our descriptive findings and cases studies of Brazil, El Salvador, and Uruguay also provide some hints at possible drivers of militarized COVID-19 governance and its short-term impact on democratic governance. We found that the pandemic accelerated military participation in governance. However, the military usually acted on the initiative and according to the directives of civilian leaders. We find that military COVID-19 activities are less likely to cause damage to democratic civil-military relations, if they are limited to policy implementation and exclude enforcing punitive COVID-19 measures in the realm public security.